2013
DOI: 10.2458/azu_js_rc.55.16378
|View full text |Cite
|
Sign up to set email alerts
|

Dating Charred Remains on Pottery and Analyzing Food Habits in the Early Neolithic Period in Northeast Asia

Abstract: ABSTRACT. This study reconstructs food habits through carbon and nitrogen isotope analysis, and C/N analysis of charred residues inside pottery from Amur River sites in Russia (Goncharka 1 site, Novotroitskoe 10 site, Kondon 1 site) and in Hokkaido, Japan (Taisho 3 site, Yachiyo A site). We obtained dates from 12,330 to 7920 BP for these sites. There are major differences in the carbon and nitrogen isotope ratios between the Taisho 3 site ( 13 C: -21.7 to -24.1‰;  15 N: 11.9-14.7‰) and the other sites ( 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…The δ 15 N values of 75% of charred deposits analyzed ranged between 8.8‰ and 13.4‰ ( range has been previously observed in charred ceramic deposits from different coastal archaeological sites associated with the exploitation of fish and marine mammals (22,23), and is more consistent with reference tissues from aquatic organisms than terrestrial animals or plants (24), although mixing of the latter cannot be ruled out or accurately quantified using this approach. We note, however, that over 90% of the samples have atomic C:N ratios less than 12 (median = 9.7) (Table S1), which characterize protein rich foods rather than starchy plants (20). Charred deposits more depleted in 15 N (i.e., below 6‰) and consistent with terrestrial plant and animal foods were only observed in the minority of cases (approximately 8% of observations).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The δ 15 N values of 75% of charred deposits analyzed ranged between 8.8‰ and 13.4‰ ( range has been previously observed in charred ceramic deposits from different coastal archaeological sites associated with the exploitation of fish and marine mammals (22,23), and is more consistent with reference tissues from aquatic organisms than terrestrial animals or plants (24), although mixing of the latter cannot be ruled out or accurately quantified using this approach. We note, however, that over 90% of the samples have atomic C:N ratios less than 12 (median = 9.7) (Table S1), which characterize protein rich foods rather than starchy plants (20). Charred deposits more depleted in 15 N (i.e., below 6‰) and consistent with terrestrial plant and animal foods were only observed in the minority of cases (approximately 8% of observations).…”
Section: Resultsmentioning
confidence: 96%
“…Similarly high δ 15 N values have been found in charred deposits on Jōmon pots throughout the Japanese archipelago (9,19,20). Lipid residue analysis has shown that marine and freshwater products were frequently processed in pottery produced by Holocene hunter-gatherers from Northeastern North America (22) and the Baltic (23,41), and in Japan as late as the Final Jōmon phase (1000-400 B.C.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, δ 13 C and δ 15 N values were obtained on 157 samples from 21 sites (Fig. 3C), which were complemented with previously published data undertaken as part of AMS radiocarbon ( 14 C) dating programs (40,41). As with δ 13 C 16:0 , a broader range of nitrogen isotope values was obtained from the Initial Jōmon pottery [Incipient variance, σ 2 = 5.6, n = 119; Initial variance, σ 2 = 10.9, n = 71; Brown-Forsythe test F(1,188) = 13.49; P = <0.005].…”
Section: Holocene Pottery Used For Processing Of a Wider Array Of Aqumentioning
confidence: 99%
“…Kunikita et al . (2013) have employed isotope analysis of charred residues to confirm that the oldest pottery in Hokkaido was used for the processing of aquatic resources. Through the extensive application of lipid analysis to early pottery in the Japanese archipelago, Craig et al (2013) and Lucquin et al .…”
Section: Research Historymentioning
confidence: 99%